2017
DOI: 10.1111/1751-7915.12783
|View full text |Cite
|
Sign up to set email alerts
|

Microbial approaches for targeting antibiotic‐resistant bacteria

Abstract: SummaryAntibiotic resistant bacterial infections are a global public health challenge that has been increasing in severity and scope for the last few decades. Without creative solutions to this problem, treatment of injuries and infections will become progressively more challenging. A better understanding of the human microbiome has led to a new appreciation for the role commensal microbes play in protecting us from pathogens, especially in the gut. Antibiotics lead to disruption of the gut microbial ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Bacteriophages represent the major viral components of the GM and contribute to several GM features, such as microbial composition and diversity as well as horizontal gene transfer [105][106][107][108][109]. Bacteriophages directed against specific bacterial strains can be another viable option against AMR [110]. Bacteriophages show efficacy against biofilm-associated infections, such as methicillin-resistant Staphylococcus aureus [111] and P. aeruginosa infections [112].…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Bacteriophages represent the major viral components of the GM and contribute to several GM features, such as microbial composition and diversity as well as horizontal gene transfer [105][106][107][108][109]. Bacteriophages directed against specific bacterial strains can be another viable option against AMR [110]. Bacteriophages show efficacy against biofilm-associated infections, such as methicillin-resistant Staphylococcus aureus [111] and P. aeruginosa infections [112].…”
Section: Bacteriophagesmentioning
confidence: 99%
“…In terms of gut microbiome restoration, microbiomemodulating therapy has been reported on to improve "colonization resistance" against drug-resistant bacteria. Wong et al undertook a pooled analysis from 101 patients (18 studies) that underwent fecal microbiota transplantation (FMT) and found that 82% achieved decontamination or significant reduction in carriage of multidrug-resistant bacteria [127]. Based on favorable results with FMT in patients with C. difficile, interest in microbiome-modulating therapies is increasing [128][129][130][131].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…(i) microbial biosensors for diagnosis, monitoring and epidemiology (Chang et al, 2017), (ii) nutritional therapy for persistent diarrhoea (Sarker et al, 2017), (iii) new therapeutic strategies for treatment of infections caused by drug-resistant microbes (Br€ ussow, 2017;Wong and Santiago, 2017) and recurrent infections by persister cells and biofilms (Wood, 2017), (iv) the use of designed bacteria to deliver therapeutics (Alvarez and Fernandez, 2017), (v) use of metal-based antimicrobials (Turner, 2017), (vi) microbiome therapies (Cryan, 2017;O'Toole and Paoli, 2017;Osman, 2017), (vii) use of synbiotics (synergistic combinations of prebiotics and probiotics) in prevention and therapy (Gurry, 2017), (viii) tumour-targeting bacteria-based cancer therapies (Felgner et al, 2017), and (ix) the use of microbial treatment of clinical environment surfaces to reduce drug-resistant pathogen burdens (Caselli, 2017) The BKH is thus a crucial motor of medical advancement and its translation into clinical practice. It will also counteract the current trend in expertise fragmentation and lead to more holistic assessments of patient symptoms, and result in the replacement of linear sequential trial-and-error decision tree treatment schedules, based on patient responses to conventional practice drugs, by treatment schedules based on comprehensive exploration of the multidimensional space of personalized medicine that considers patient genomics/microbiome/ physiology/health status/lifestyle, and all available intervention options and their predicted consequences for different individuals.…”
Section: National Clinical Informatics Centre (Ncic)mentioning
confidence: 99%
“… microbial biosensors for diagnosis, monitoring and epidemiology (Chang et al ., ), nutritional therapy for persistent diarrhoea (Sarker et al ., ), new therapeutic strategies for treatment of infections caused by drug‐resistant microbes (Brüssow, ; Wong and Santiago, ) and recurrent infections by persister cells and biofilms (Wood, ), the use of designed bacteria to deliver therapeutics (Alvarez and Fernandez, ), use of metal‐based antimicrobials (Turner, ), microbiome therapies (Cryan, ; O'Toole and Paoli, ; Osman, ), use of synbiotics (synergistic combinations of prebiotics and probiotics) in prevention and therapy (Gurry, ), tumour‐targeting bacteria‐based cancer therapies (Felgner et al ., ), and the use of microbial treatment of clinical environment surfaces to reduce drug‐resistant pathogen burdens (Caselli, ) …”
Section: The Components Of the New Healthcare Clustermentioning
confidence: 99%